IBM PENGUATAN DAYA SAING BERKELANJUTAN PADA KELOMPOK BUDIDAYA IKAN LELE DI PUGER -JEMBER - Diana Dwi Astuti; Tamriatin Hidayah; Hamzah Fansuri (RELASI : JURNAL EKONOMI, 2013)
Science and technology for the Community (Iptek bagi Masyarakat/IbM) can be used as a vehicle in community service activities to actively improve the efficiency and productivity of businesses partners, and is the  application of science and technology by implementing and lecturers can provide experiences for students that entrepreneurship has the insight and knowledge in order to foster the entrepreneurial spirit. Implementation of the activities carried out through the joint  identification of  problems  between  partners,  implementing  faculty  and students. Based on the problems identified priority considering it is made in time and cost. The conclusion that can be drawn  from  the implementation of  IBM, is the presence  of unresolved  issues  due to time constraints  and  the  cost  of production  lay out,  while've  accomplished is  making  catfish  feed  (pellets), diversification of processed catfish (shredded, chips, nuggets), support tools (tool maker  catfish  feed  /  pellets,  presto,  pans,  pots,  tools  shredded  pres,  pres  plastic tool, blender), catfish care, and managerial aspects. The need for these activities to be continued in order to provide more benefits for partners mainly because, the desire to continue this activity is the input from partners and as also suggested by the reviewer as business partners to conduct monitoring in Jember.